Clinical Aspects of Using of Etiotropic Immunotherapy in Complex Treatment of Patients with Acute Optic Neuritis Associated with Herpesvirus Infection - D. A. Povaliaeva; V. V. Egorov; G. P. Smoliakova; L. P. Danilova (Oftalʹmologiâ, 2018)
Purpose. To study the clinical effectiveness of the system of complex treatment of optic neuritis (ON) associated with herpesvirus infection(HVI), including methods of immunopharmacotherapy. Patients and methods. The clinical study involved 55 people (55 eyes) with acuteON associated with HVI. The treatment regimen for all patients included 10 days the addition of Dexamethasone solution to optic nerve on decreasing scheme, Emoxypine 1% 0.5 ml, and Dicynone 12.5% 0.5 ml through irrigation system implanted in retrobulbar space, in combination with appoint of neuroprotective drugs (Picamilon and Semax). Depending on features of immunotherapy, all patients were divided into 3 groups. The first group consisted of 20 patients, whose treatment in addition to the above included intravenously infusions 6 mg of Polyoxidonium from the moment they entered the eye hospital. The second group included 17 patients who received in addition to Polyoxidonium, muscle injections of Cycloferon, in mode and doses according to the manufacturer's instructions. The third group of patients (18 peoples) — with using etiotropic immunotherapy that consisted of combination of Polyoxidonium, Cycloferon and endonasal electrophoresis of 0.25% solution of Derinat. The duration of immunotherapy was 10–12 days. Results. The analysis of obtained datas showed that more significant positive dynamics was noted in the clinical course of ON in patients of the 3rd group of observation, who simultaneously received complex of 3 immunotropic drugs in comparison with group 1 and 2, in the treatment of which we used one immunotropic drug Polyoxidonium, or its combination with Cycloferon, without Derinat. Conclusions. The method of etiotropic and pathogenetic immunotherapy developed by us, represented by the combination of Polyoxidonium, Cycloferon and Derinat, at ON, associated with herpesvirus infection, allows to shorten by 2 times or more the period of stopping of signs of inflammation in optic nerve, to exceed the average visual acuity in the period of clinical recovery by 0.5–1.3 times and improve functional results of treatment in the absence of recurrence of the disease within 1 year of observation